Isolation of Lignin from Anaerobically Digested Unhydrolyzed Solids Produced in a Biorefinery - Xiaoyu Tang; Kunyang Zhao; Chunlin Gao; Xionghui Gao; Venkatesh Balan; Wenguo Wang (Agriculture, 2022)
About 30–40% of lignin-rich unhydrolyzed solids (UHS) are left behind after subjecting lignocellulosic biomass to thermochemical pretreated processes followed by enzymatic hydrolysis (EH) to produce sugars that are fermented to fuels and chemicals in a biorefinery. Ammonia Fiber Expansion (AFEX) is one of the leading alkaline pretreatment processes that use volatile ammonia that can be recovered and reused beneficially for the environment. In this work, we used AFEX-EH-UHS which are produced after subjecting corn stover to AFEX followed by EH and contain carbohydrates, ashes, and other impurities that are detrimental to the conversion of lignin to high-value products. In the study, we discovered that ~80% of the carbohydrates present in AFEX-EH-UHS were hydrolyzed and consumed during the AD process. The resulting solids, hereafter called AD-UHS, were subjected to lignin extraction using different combinations of solvents under reflux conditions. The solvent-extracted lignin was subjected to thermogravimetry, nuclear magnetic resonance (NMR) spectroscopy, and molecular weight analysis. Among the solvents, acetic acid could produce 95% pure lignin with some chemical modification, while aqueous ethanol was able to produce 80% pure lignin without any chemical modification.